A Metabolomics-Inspired Strategy for the Identification of Protein Covalent Modifications - Nunes, João (2019)
This work was supported by Fundação para a Ciência e a Tecnologia (FCT), Portugal, through projects UID/QUI/00100/2019, IF/01091/2013/CP1163/CT0001 and PTDC/QUIQAN/32242/2017 as well as doctoral fellowships SFRH/BD/102846/2014 (to CC) and SFRH/BD/140157/2018 (to JN);joint funding from FCT and the COMPETE Program is also acknowledge through RNEM-LISBOA-01-0145-FEDER-022125-funded postdoctoral fellowship (to JM).